Trend of chickenpox incident cases through absent vaccination in Najaf Governorate-Iraq from January 2009 to May 2014 - Abdulkareem A. Mahmood; Tamara M. Ibrahim (Kufa Journal for Nursing Sciences)
Background: Chickenpox infection is a common and highly contagious viral disease caused by the varicella zoster virus. It is highly endemic disease with increasing annual incidence in absence of varicella immunization program in Iraq. The predominance of uncomplicated cases in children tends to overshadow the morbidity associated with social and economic burden of families in addition to risk of complication in younger age groups. Chickenpox now has been considered one of the most common vaccine-preventable diseases in many countries including Iraq.